Development of method of emitter application on the electrodes of gas-discharge lamps with preliminary heating - Ківа, О. В.; Стасюк, Т. О.; Ходурський, В. Є. (Scientific Progress & Innovations, 2012)
The method of emitter application on the electrodes of gasdischarge lamps by dipping them in the emitter suspension with preliminary heating has been developed. Experimental studies were carried out on electrodes of DRL-250 lamps on study the effect of preliminary heating on emitter weight gain, applied on the electrode and the degree of filling electrode internal cavities with emitter on the base of which the technology of emitter application on the electrodes of gas-discharge lamps with the preliminary heating has been offered. The article also gives the results of experimental tests and obtained the comparative characteristics for methods of applying the emitter on electrodes in HID lamps with the preliminary heating.